2011
DOI: 10.2533/chimia.2011.250
|View full text |Cite
|
Sign up to set email alerts
|

Functional Group Distributions on Mesoporous Silica

Abstract: Functional group distributions on mesoporous silica Brühwiler, D (2011 Functional group distributions on mesoporous silica Abstract Most applications of mesoporous silica require some degree of functionalization. The surface of porous materials can be divided into external and internal (pore) surfaces, and in many cases, a selective functionalization of these surface subsections is desired. This short review outlines our recent work in this field and focuses on the postsynthetic functionalization of mesoporou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Later studies by Gartmann and Brühwiler et al used confocal laser scanning microscopy (CLSM) to image the distributions of organic functionalities grafted onto porous silica host materials after coupling with appropriate fluorescent labels. [58][59] They showed that the loading and distribution of functional groups depended on their size and the pore diameter, as well as solvent polarity. In small-pore materials, selective grafting of the external surface could be achieved using a large orgnanoalkoxysilane precursor, such as 3-aminopropyltris(methoxyethoxyethoxy)silane (APTMEES), and a non-polar solvent (see Figure 4, left).…”
Section: Yoshitake Et Al Estimated the Spacing Between 3-bromopropylmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies by Gartmann and Brühwiler et al used confocal laser scanning microscopy (CLSM) to image the distributions of organic functionalities grafted onto porous silica host materials after coupling with appropriate fluorescent labels. [58][59] They showed that the loading and distribution of functional groups depended on their size and the pore diameter, as well as solvent polarity. In small-pore materials, selective grafting of the external surface could be achieved using a large orgnanoalkoxysilane precursor, such as 3-aminopropyltris(methoxyethoxyethoxy)silane (APTMEES), and a non-polar solvent (see Figure 4, left).…”
Section: Yoshitake Et Al Estimated the Spacing Between 3-bromopropylmentioning
confidence: 99%
“…38,62 The CLSM imaging also demonstrated that trace amounts of water in the organic solvents used during grafting can lead to clustering of organosilanes and nonuniform distribution of functional groups on surfaces (Figure 4, right). [59][60] and studied their locations by observing Si and W using the EFTEM. 65 The elemental mapping showed patterns of alternating Si-rich and W-rich domains, which indicated that the organometallic tungsten complexes are located inside the channels of the mesoporous silica materials.…”
Section: Yoshitake Et Al Estimated the Spacing Between 3-bromopropylmentioning
confidence: 99%
“…This study shows that the surface properties of functionalized mesoporous silica play an important role in UV protection. In other words, functional molecules used to modify mesoporous materials are crucial [20]. Compared with other biomolecules and organic molecules, peptides containing natural amino acids are widely used as surface modification units because of their inherent bioactivity, biodegradability, and biocompatibility [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the typical silanes used as APTES or APTMEES (3-aminopropyltriethoxysilane or 3-aminopropyltris methoxy ethoxy ethoxy silane, respectively) are quite expensive and usually affects the pore lead to decreasing mesoscopic order. 8 W Limbut et al 9 proposed in 2004 a method to immobilize urease on three different support based on SiO 2 for the determination of urea 9 and they showed the high efficiency of such interaction. Therefore, in this work we propose an innovation in the traditional method 10,11 for anchoring glucose-sensing molecules on an inorganic substrate using modified powdered silicate glasses as micrometric inner substrate, which is a very economical substrate and environmental friendly and anchoring a sensing molecules through an innovative and green chemical substance such is the urea.…”
Section: Introductionmentioning
confidence: 99%